2021
DOI: 10.3390/ijerph18158109
|View full text |Cite
|
Sign up to set email alerts
|

The Acute Effects of a Swimming Session on the Shoulder Rotators Strength and Balance of Age Group Swimmers

Abstract: The purpose of this study was to analyze the acute effects of a standardized water training session on the shoulder rotators strength and balance in age group swimmers, in order to understand whether a muscle-strengthening workout immediately after the water training is appropriate. A repeated measures design was implemented with two measurements performed before and after a standardized swim session. 127 participants were assembled in male (n = 72; age: 16.28 ± 1.55 years, height: 174.15 ± 7.89 cm, weight: 63… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
2
2

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 26 publications
(47 reference statements)
1
2
2
Order By: Relevance
“…However, only the changes in the dominant side of national swimmers were significant. Contrary to the result of this study, Batalha et al 13 found no changes in shoulder ER:IR ratio after a swim-training session in competitive swimmers. This might be explained as the intensity of the session in the present study was high, whereas in Batalha et al 13 study was medium to low.…”
Section: Shoulder Rotation Torquecontrasting
confidence: 99%
See 3 more Smart Citations
“…However, only the changes in the dominant side of national swimmers were significant. Contrary to the result of this study, Batalha et al 13 found no changes in shoulder ER:IR ratio after a swim-training session in competitive swimmers. This might be explained as the intensity of the session in the present study was high, whereas in Batalha et al 13 study was medium to low.…”
Section: Shoulder Rotation Torquecontrasting
confidence: 99%
“…Contrary to the result of this study, Batalha et al 13 found no changes in shoulder ER:IR ratio after a swim-training session in competitive swimmers. This might be explained as the intensity of the session in the present study was high, whereas in Batalha et al 13 study was medium to low. Several authors have also investigated the changes in this ratio over a longer period, [34][35][36] reporting reductions between 4% to 14% during a training period in young competitive swimmers.…”
Section: Shoulder Rotation Torquecontrasting
confidence: 99%
See 2 more Smart Citations
“…6 The reduction in the shoulder motion, internal and external rotation, might be due to rotator cuff degeneration or overuse and thus resulted in pain and reduced level of satisfaction of shoulder functioning in swimmers. 6,25 A study showed results between disability and pain which coincides with a study by Tate and his team.…”
Section: Discussionsupporting
confidence: 80%